(untitled) (Encuentros, 2023)
This article attempts to structure a literature review around teacher identity as a growing field in educational research. Methodologically, the narrative review of literature is appropriated, defining the category from four lines: conceptualization, structure, configuration during teacher training, and other implications. It was founded 165 international publications, of which 47 were selected because of relevance and impact in this field. The results show the polysemy of the concept, as well as its complexity in terms of endogenous and exogenous factors that intervene in the process, in addition, exchanges between professional identity and personal identity are highlighted. It made possible to conclude the need to examine teacher identity from contextual conditions of each Nation since in these a status quo of the profession is established that is definitive, the role of teacher training in this identity constitution is recognized and its mutable and contingent condition is emphasized.